2017
DOI: 10.19082/4820
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between social support, self-efficacy and health-promoting behavior in hemodialysis patients hospitalized in Karaj in 2015

Abstract: BackgroundIn hemodialysis, as a choice of treatment due to long treatment duration, the patient encounters limitations. Perceived social support, perceived self-efficacy and health promoting activities are important strategies to facilitate and maintain their health.AimTo determine the correlation between social support, self-efficacy and health promoting behaviors in hemodialysis patients hospitalized in Karaj city in 2015.MethodsThis cross-sectional descriptive correlational study was carried out on 200 hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 11 publications
4
20
1
Order By: Relevance
“…Based on our results, two options, "good" (50%) and "moderate" (31%) were found to be higher in healthy people, while the option "poor" was lower in healthy people (18%) than in type II diabetics (50%). The studies by Shojaeizadeh et al, Estebsari et al and Tol et al, in 2012 was consistent with the findings of this study (17,21,27,29,30).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Based on our results, two options, "good" (50%) and "moderate" (31%) were found to be higher in healthy people, while the option "poor" was lower in healthy people (18%) than in type II diabetics (50%). The studies by Shojaeizadeh et al, Estebsari et al and Tol et al, in 2012 was consistent with the findings of this study (17,21,27,29,30).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies were consistent with our results (1,17,22,31). Studies have shown that low physical activity is one of the major risk factors for diabetes, since, moderate or high physical activity is associated with a reduction in the risk of type II diabetes (29,30).…”
Section: Discussionsupporting
confidence: 90%
“…The results of other studies have also confirmed this finding. 22,29,30,31 Pregnant women's greater awareness about the positive outcomes of healthpromoting behaviors increases their intention to adopt these behaviors. Higher social support also leads to the greater adoption of health-promoting behaviors in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, nurses spend the most time with patients undergoing hemodialysis and can impact their health outcomes. [22][23][24] For instance, nurses can educate patients to change their lifestyle and habits, and reduce their needs to emergency hemodialysis sessions. 25 Also, nurses have a responsibility for the provision of mental health support to hemodialysis patients, and prevention of further psychological problems due to the underlying disease.…”
Section: Relieving Anxiety and Depression In Hemodialysis Patientsmentioning
confidence: 99%
“…Grigoriou et al believe that the treatment of depression in hemodialysis patients should be a multidimensional approach with the application of different strategies drawing on the skills of the healthcare team. Accordingly, nurses spend the most time with patients undergoing hemodialysis and can impact their health outcomes . For instance, nurses can educate patients to change their lifestyle and habits, and reduce their needs to emergency hemodialysis sessions .…”
Section: Introductionmentioning
confidence: 99%